Three-dimensional spheroid culture of human gingiva-derived mesenchymal stem cells enhances mitigation of chemotherapy-induced oral mucositis - Zhang, Qunzhou; Nguyen, Andrew L; Shi, Shihong; Hill, Colin; Wilder-Smith, Petra; Krasieva, Tatiana B; Le, Anh D (Stem cells and development, 2012)
Mesenchymal stem cells (MSCs) are capable of regenerative and immunomodulatory functions in cell-based therapies in a variety of human diseases and injuries; however, their therapeutic efficacy and potential side effects remain major obstacles in clinical applications. We report here a 3D spheroid culture approach to optimize stem cell properties and therapeutic effects of human gingiva-derived mesenchymal stem cells (GMSCs) in mitigation of experimental oral mucositis. Under growth condition of ultra-low attachment, GMSCs spontaneously aggregated into 3D spheroids and exhibited distinct early stem cell phenotype characterized by elevated expression Stro-1 and CXC chemokine receptor 4 (CXCR-4) as well as OCT-4 and Nanog, 2 important transcriptional factors relevant to stem cell properties, and decreased expression of MSC-associated markers, including CD29, CD90, and CD105. Functionally, spheroid GMSCs are capable of enhanced multipotency and augmented secretion of several chemokines and cytokines relevant to cell migration, survival, and angiogenesis. More importantly, spheroid GMSCs expressed increased levels of reactive oxygen species, hypoxia-inducible factor (HIF)-1 and -2α, and manganese superoxide dismutase, which correlated with improved resistance to oxidative stress-induced apoptosis. Using an in vivo murine model of chemotherapy-induced oral mucositis, we demonstrated that spheroid-derived GMSCs possessed better therapeutic efficacy than their adherent cells in reversing body weight loss and promoting the regeneration of disrupted epithelial lining of the mucositic tongues. These findings suggest that 3D spheroid culture allows early stemness preservation and potentially precondition GMSCs for enhanced mitigation of oral mucositis.